The Influence of Democratic Leadership Style and Quality of Work Life on Science Teacher Performance - Ferdiansah, Renaldi; Ismaya, Bambang; Wahyudin, Undang Ruslan (Integrated Science Education Journal, 2025)
Purpose of the study: This study investigates the influence of democratic leadership style and quality of work life (QWL) on teacher performance in junior high schools. Methodology: The research was conducted using a quantitative approach with a causal-associative design, involving 65 teachers from two schools in Tempuran Subdistrict, Karawang. Data were collected through validated and reliable questionnaires and analyzed using multiple regression. Main Findings: The findings reveal that both democratic leadership style and QWL have a positive and significant effect on teacher performance, both partially and simultaneously, with a combined contribution of 52.4%. These results underscore the importance of participatory leadership practices and teacher well-being in enhancing professionalism and productivity within educational settings. Novelty/Originality of this Study: The novelty of this research lies in its integration of leadership and QWL into a single analytical model, whereas most prior studies examined these variables independently. By situating the study within the context of regional public schools, it offers new perspectives on educational management in environments that often face resource and welfare challenges. The implications are substantial for school principals and policymakers, as the findings highlight the need to strengthen human-centered leadership practices and establish supportive work conditions that foster job satisfaction, recognition, and commitment, ultimately improving student learning outcomes.